Pembelajaran Fisika Dengan Video Rekam Layar Pada Masa Pandemi Covid-19 Untuk Mengoptimalkan Kemampuan Belajar Siswa Kelas XII-MIPA.1 Pokok Bahasan Listrik Dinamis SMA Negeri 2 Bangkalan - Mohammad Saeri (FKIP, Universitas Billfath Lamongan, 2020)
The purpose of using this screen recording application is to improve the ability of physics knowledge class XII-MIPA.3 students of SMAN 2 Bangkalan 2020/2021. This research uses the Classroom Action Research (CAR) method. Each cycle in CAR begins with a plan, then continues with implementation, observation and reflection. The subjects of this study were 34 students of class XII-MIPA.3 Sman 2 Bangkalan. Data were collected using the results of student knowledge tests, and analyzed descriptively quantitative. From the results of the study, it can be concluded that the use of video screen record can improve the ability of students of class XII-MIPA knowledge.3 SMAN 2 Bangkalan in the learning process of physics. By providing variations of learning using video screen record and encouraging students to study groups an increase in the results of students' abilities in the first, second, and third cycle. By limiting the KKM 70, the percentage of completeness of knowledge 17.64% in the initial stages becomes 45% as a result of the first action. This result is still very far from the target of 75% completeness. So in the second action many improvements were made, including by preparing material in the form of power points and explaining them using screen record video. In addition, there is also an emphasis on optimizing the use of available learning resources, both from books and the internet. This step has a very significant influence on students 'knowledge abilities, as evidenced by completeness of students' knowledge abilities as a result of this second action increased sharply to 69%. The third action was carried out many improvements, including by simplifying the summary of material, and repeated emphasis on understanding rather complex concepts by using screen recordings, especially in the discussion of questions. This shows that there is always an increase in the percentage of completeness in the value of students 'knowledge ability to be 89% Similarly, aspects of students' knowledge ability is always increasing.